2013
DOI: 10.1093/ajh/hpt081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antihypertensive Drugs on Central Blood Pressure in Humans: A Preliminary Observation

Abstract: background Central blood pressure (BP) is considered a better predictor of cardiovascular events than brachial BP. Modifications of central, beyond brachial BP, can be assessed by pressure amplification, a potential new cardiovascular risk factor. Comparison between drugs' effect on central hemodynamics has been poorly studied. Our aim was to assess the hemodynamic effect of a 12-week treatment with amlodipine 5 mg, or candesartan 8 mg, or indapamide sustained-release 1.5 mg, in comparison with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
1
21
0
5
Order By: Relevance
“…Some studies have shown different effects of antihypertensive treatment on central and brachial blood pressure. 18,19 However, recently the X-CELLENT study was unable to show different central and peripheral blood pressure effects by indapamid, candesartan, and amlodipine, 20 as did the CHAMPION trial comparing beta-blockers with different receptor affinities. 21 Thus, some, but not all, antihypertensive medications may exert different effects on central and brachial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown different effects of antihypertensive treatment on central and brachial blood pressure. 18,19 However, recently the X-CELLENT study was unable to show different central and peripheral blood pressure effects by indapamid, candesartan, and amlodipine, 20 as did the CHAMPION trial comparing beta-blockers with different receptor affinities. 21 Thus, some, but not all, antihypertensive medications may exert different effects on central and brachial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…When valsartan was compared to captopril, the two drugs equally reduced PWV as well as Aix [42]. As far as Aix reduction is concerned, losartan (see the LIFE (Losartan Intervention For Endpoint reduction in hypertension) [43] and OPTIMAAL (Optimal Trial in Myocardial Infarction with Angiotensin Antagonist Losartan) [44] studies) and candesartan [45, 46] were proven to reduce it. Other ARBs, such as valsartan (the VALUE (Valsartan Antihypertensive Long-Term Use Evaluation) study) [4749], olmesartan [50], telmisartan [51], and eprosartan [52], were proven to reduce central blood pressure more than the systolic blood pressure and increase pulse pressure, while reducing Aix and PWV.…”
Section: Influence Of Drugs On Arterial Stiffnessmentioning
confidence: 99%
“…The largest amount of evidence is for the dihydropyridine calcium channel blocker amlodipine [32, 34, 37, 46, 49, 55]. This drug was evaluated in the CAFÉ study, among other trials, where it proved to reduce central blood pressure more than peripheral blood pressure; it amplified pulse pressure and reduced Aix and PWV, thus displaying its destiffening effect [32].…”
Section: Influence Of Drugs On Arterial Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analysis by the type of drugs taken by controls revealed significant reductions in SBP for comparisons of ARBs with placebo (WMD = − 3.81 mm Hg; 95% CI: − 6.70 to − 0.91; P = 0.010; I 2 = 77.2%) and diuretics (WMD = − 1.31 mm Hg; 95% CI: − 2.33 to − 0.27; P = 0.013; I 2 = 0.0%), and reductions in diastolic blood pressure for placebo 23 Caucasian Hypertension cfPWV Parallel Open Candesartan Placebo 33 35 12 Abbreviations: ACEI, angiotensin converting enzyme inhibitor; ARB, angiotensin receptor blocker; baPWV and cfPWV, brachial-ankle and carotid-femoral pulse wave velocity; CCB, calcium channel blocker; NA, not available; RAS, renin-angiotensin system.…”
Section: Changes In Pulse Wave Velocitymentioning
confidence: 99%